Diversity of Foraminifera from the Indian Coast - Devre, Rushikesh V.; Shetty, Ashwit S.; JosephKennady, Toni; Shingadia, Hitesh U. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Foraminifera, members of the class Granuloreticulosa, are marine protozoans distributed across both pelagic and benthic zones of the ocean. After the death of these microscopic organisms, their shells are washed along the intertidal sandy shores along with sand granules. This organism's shell is called a test which is composed of calcium carbonate, silica, or agglutinated materials that characterize the genera of Foraminifera. In the present study, the sand samples were collected along the different sites of the Indian coastline viz. Juhu Beach (Mumbai), Alibaug Beach (Raigad), Palolem Beach (Goa), Kanyakumari Beach (Tamil Nadu), and Puri Beach (Odisha). In this study, samples from Juhu Beach showed the highest foraminiferan diversity (24%) followed by Alibaug (21%) > Kanyakumari = Puri (19%) > Goa (17%). Across all selected study sites, the prevalence of specimens from the Globothalamea class was notable, comprising 39% of the total foraminiferans. This was followed by Monothalamae (26%), Fusulinata (13%), Tubothalamea (11%), and Nodosariata (11%). 13 extinct genera were also documented in the study.